Frequency of Microsatellite Metastases, Satellite Metastases, and Residual Tumor in Thin Melanomas: A Retrospective Cohort Study - Ebba Wennberg; Rudy Bittar; Helena Svensson; John Paoli (Dermatology Practical & Conceptual)
Introduction: Thin invasive melanomas (Breslow thickness ≤1.0 mm) are increasing in incidence in Sweden, but also notably have a favorable prognosis. Treatment typically involves complete diagnostic excision followed by wide local excision (WLE) to eliminate potential microsatellite and satellite metastases, along with residual melanoma.